Dal nichilismo verso una religione post-moderna. Le proposte storiografiche di W. Weischedel e J.Schellenberg - Damonte, Marco (Bollettino Filosofico, 2015)
The aim of this paper is to compare W. Weischedel’s and J.L. Schellenberg’s philosophies of religion. In spite of the independence of their speculations, both use the same sources and have the same objective: proposing a philosophy of religion useful in the post-modern world. In order to do this, I will take Weischedel’s passage from nihilism to scepticism into consideration and then I will analyze his different conceptions of religious scepticism. In the analytic philosophy, Schellenberg’s trilogy proposes a similar passage suggesting that it is necessary to go beyond the contrast between theism and atheism, to appreciate the value of an epistemic scepticism able to characterize a new satge of religion. In both cases, scepticism assumes a constructive value. I will conclude that the different contexts in which these proposals have originated, make them compatible to underline the anthropological merit of religion and to formulate a philosophy of religion fit to avoid rationalism and fideism.